FAMILY PSYCHOEDUCATION FOR SCHIZOPHRENIA PATIENTS: A LITERATURE REVIEW - Hilfida, Nurullia Hanum; Kholis, Anja Hesnia; Lailiah, Novianti; Septanto, Aby Nugrah; Saudi, La (Jurnal Ilmu Keperawatan, 2024)
Family psychoeducation provides in-depth information about schizophrenia, enabling families to better understand the patient's condition while alleviating their emotional distress. This intervention benefits not only patients but also their families by enhancing their understanding and skills in supporting the treatment process. Objective: To identify and summarize key findings from studies examining the effectiveness of family psychoeducation as an intervention for schizophrenia patients. Methods: This review employed a literature review methodology, with data collected from databases including PubMed, ScienceDirect, ProQuest, and Google Scholar. The search utilized relevant keywords, and the extracted data were analysed using the PICO framework, focusing on study characteristics, types of interventions, and outcomes. Reporting adhered to the PRISMA-SR guidelines. Included studies were English language randomized controlled trials (RCTs) that specifically addressed family psychoeducation for caregivers of schizophrenia patients and reported outcomes such as reduced caregiver burden, improved caregiving knowledge, and skills. Results: There were 17 articles containing 8 types of psychoeducational program that can be caried out on families of schizophrenia patients, namely Multifamily Psychoeducational Program, WeChat-based integrative family intervention program, Telehealth-Based Psychoeducation for Caregivers, Behavioral Family Psychoeducational Program, Mindfulness-Based Psychoeducation, Structured Psychoeducation, Family Psychoeducation, Group Psychoeducation. The intervention was given for a minimum of 4 sessions, and a maximum of 16 sessions. Conclusion: Family psychoeducation is an effective approach for improving family understanding, caregiving skills, and the quality of life for patients and families.